BENTUK, MAKNA DAN FUNGSI PEMALI PADA PERILAKU MASYARAKAT PESISIR KABUPATEN MAROS: PENDEKATAN SEMIOTIK - Ramli, Muhammad; Rahman, Nurhayati; Gusnawaty, Gusnawaty (JURNAL ILMU BUDAYA, 2019)
This research aims to describe the forms of pemali as the value of local wisdom in the Maros of District in Bontoa and Maros Baru sub-district, analyze how the meaning of pemali on the behavior of coastal communities in Maros of District, and how the function of the pemali towards local wisdom is in the behavior of the coastal communities of Maros District.The method used in this study is a qualitative method that is describing the form, function and meanings of verbal and non-verbal pemali.  Data collection was conducted through surveys and direct interviews with coastal communities in Maros of District. The results of this study indicate that. Verbal form the guards of pemali in coastal communities of Maros District, including: The words Cappu/Tena/De’gaga (completed), Tassala (detached), Pettu (broken off) Cappak (butt end), and Mate (dead) aqgeaq-geaq (be at odds), Abbaju eja je’ne-je’ne ri tamparanga and (bathing on the beach using red clothes) Appoloi bangi, (whistle). And the of non-verbal pemali coastal communities in Maros District, including; Tettong ribawang/Ammenteng  ritimungang, (stand at the door) Aqboko (backward). Tinro mopang atau tinro mappang, (sleep face down). Appatinompang (face down the container), Pasampo ulu atau Songko Punggawa,  (headgear). Nipiralluangi pa’riolo kanang, (step with your right foot), the meaning of pemali shows religious meaning and social meaning and the function of pemali shows that the function is to protect oneself and as a function of culture.